Proposed Features of a Sovereign Debt Restructuring Mechanism. (Policy Papers; Policy Paper ;, 2003)
This paper follows up on the Executive Board's December 2002 discussion of the design of the Sovereign Debt Restructuring Mechanism and seeks to make further progress on the formulation of a concrete proposal for a statutory sovereign debt restructuring mechanism.